Formulasi Dan Evaluasi Sediaan Tablet Dari Ekstrak Daun Sirih Hijau (Piper Betle l.) Dengan Variasi Konsentrasi Bahan Pengikat Gelatin - Khabibah, Nurul Auliya; Ermawati, Nur (Student Scientific Journal, 2023)
Piper betle L. is one of the herbal plants that has antibacterial power due to the presence of various active substances contained therein such as essential oils, flavonoids, saponins, and polyphenols. Gelatin is added as a tablet binder to bind or attach powder particles to tablet granulation. This study aims to determine the effect of gelatin binder concentration on the physical properties of tablets and at what concentration gelatin as a binder can produce good tablets. Thick extract of green betel leaf was obtained by maceration using 96% ethanol solvent. The preparation of green betel leaf extract tablets was made with three formulas, using different concentrations of binders, including formula I containing 1% gelatin, formula II as much as 2%, and formula III as much as 3%. The method used in the manufacture of green betel leaf extract tablets is the wet granulation method. The granules obtained were tested for physical properties including flow speed and angle of repose. The tablets obtained were evaluated for physical quality including weight uniformity, hardness, size uniformity, friability, and disintegration time.Tablet formula of green betel leaf extract (Piper betle L.) with varying concentrations of gelatin binder in terms of physical quality evaluation of granules and physical quality evaluation of tablets showed that 1% gelatin concentration did not meet the requirements in the evaluation of tablet hardness and friability. At 2% concentration does not meet the requirements in the evaluation of hardness and at 3% concentration does not meet the requirements in the evaluation of disintegration time.